Understanding and assessment of ADHD: possible interlocutions between the neuropsychological and behavioral analytic approaches (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
This paper aims to present some reflections on the conceptualization and assessment of psychological disorder Attention Deficit Hyperactivity Disorder (ADHD) on the neuropsychological and behavioral analytic views. Through theoretical analysis, dialogues between the two approaches were performed basead on publications about the disorder. Regarding neuropsychology there have been probable involvement of ADHD with functional and neurochemical changes in the central nervous system and frequently cognitive studies with the executive functions. In behavior analysis there have been speculations about the involvement with verbal behavior, rule-governed behavior and self-control behavior. It was found that the two approaches are applied jointly show significant contributions to the evaluation process of the disorder: the neuropsychology by means of the instrumentalities and clinical review of diagnostic criteria and behavior analysis via functional analysis. The dialogues were possible, in conceptual and in the evaluation process.
Keywords: ADHD; Neuropsychology; Behavioral Analysis